The Effects of Regional Comprehensive Economic Partnership on Trade Openness of Lao PDR - phanla, vilakone; PHANLA, vilakone; HER, pheng; VATTHANA, mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This article aims to empirically investigate if the addition of infrastructure and FDI as control variables change the estimated coefficients for trade openness by RCEP (Regional Comprehensive Economic Partnership). Using the time series data from 2006 to 2024 and applying robust Ordinary Least Squares (OLS) estimation method, this article analyses how regionalization supported by domestic structural features is impacting Laos trade performance. The findings reveal that being an RCEP member promotes trade openness, referring to regional trade liberalization toward Laos’s deeper integration into the world economy. Trade openness is similarly positively associated with infrastructure and foreign direct investment in an economy. Yet if the combined effort of these two elements leads them to operate negatively, it means that both their benefits drop when excessive even when not jointly designed in policy. We present diagnostics that indicate the regression model is consistent with some key econometric assumptions. Its value of R-squared =0.8718 indicates its strong explanatory power. The results support Infrastructure-based and Endogenous Growth Theories, demonstrating the value of implementing national reforms consistent with regional trading agreements. Policy implications emphasize the importance of coordinated policies on infrastructure investment, FDI invitation and trade facilitation in order to maximize potential benefits from RCEP. The study contributes to the understanding of how regional economic integration could help enhance trade openness in small landlocked developing economies, and has potential powerful policy implications and lessons for interested policy makers and researchers in the area of sustainable regionalism.